1999
DOI: 10.1002/(sici)1097-0231(19990115)13:1<8::aid-rcm438>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Direct evaluation of glycated and glyco-oxidized globins by matrix-assisted laser desorption/ionization mass spectrometry

Abstract: Matrix-assisted laser desorption ionization (MALDI) mass spectrometry (MS) has been applied to achieve a qualitative and quantitative evaluation of glycated globins on a wide number of healthy and diabetic subjects. The method allowed us to establish that both alpha- and beta-globins are glycated and that, in addition to simply glycated products, other species are detected. Investigations by different sample treatments and by analysis of the glycated beta-globin fraction obtained by preparative chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 23 publications
(11 reference statements)
3
35
1
Order By: Relevance
“…The nonenzymatic glycation of immunoglobulins as a result of hyperglycemia could result in low antigen and receptor binding capacities of these antibodies. It is therefore likely that despite comparable titers, the functionality of the antibody is compromised in diabetics compared to nondiabetics (25,26). Contrary to our findings with PspA, we observed comparable titers of antibodies to all eight capsular polysaccharides tested in individuals with and individuals without diabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…The nonenzymatic glycation of immunoglobulins as a result of hyperglycemia could result in low antigen and receptor binding capacities of these antibodies. It is therefore likely that despite comparable titers, the functionality of the antibody is compromised in diabetics compared to nondiabetics (25,26). Contrary to our findings with PspA, we observed comparable titers of antibodies to all eight capsular polysaccharides tested in individuals with and individuals without diabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…Apart from peaks due to protonated α and β globins, the MALDI spectra in our study showed peaks due to glycated α and β globins, confirming our previous findings [6,7] that both globins are glycated in vivo, in contrast to the usual thinking, as reported in the literature, on the definition of HbA 1 c and its measurement [2]. HbA 1 c measurements represent the integral of all glycated α and β globins, as proven by the relatively good linear plot.…”
Section: Discussionsupporting
confidence: 92%
“…For MALDI analysis, blood samples were treated as already described [6,7]. MALDI time of flight [8] spectra were obtained using a Voyager-DE PRO instrument (Applied Biosystems, Foster City, Calif., USA) that was operating in positive ion linear mode [6,7].…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…The application of mass spectrometry to evaluation of glycated globins has the merit of demonstrating that both globins are glycated to similar extents (Lapolla et al, 1997b). MALDI can reveal the presence of glycooxidated products, which cannot be detected in ESI conditions 1999).…”
Section: Mass Spectrometry and Diabetesmentioning
confidence: 99%